2012
DOI: 10.1306/08171111061
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of pore types and networks in mudrocks and a descriptive classification for matrix-related mudrock pores

Abstract: Matrix-related pore networks in mudrocks are composed of nanometer-to micrometer-size pores. In shale-gas systems, these pores, along with natural fractures, form the flow-path (permeability) network that allows flow of gas from the mudrock to induced fractures during production. A pore classification consisting of three major matrix-related pore types is presented that can be used to quantify matrix-related pores and relate them to pore networks. Two pore types are associated with the mineral matrix; the thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
1,421
3
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,952 publications
(1,577 citation statements)
references
References 59 publications
32
1,421
3
2
Order By: Relevance
“…[2][3][4][5][6][7] The pore volume of shales can be determined by various techniques such as mercury injection capillary pressure (MICP) porosimetry and grain density/ helium pycnometry, scanning electron microscopy (SEM) images and gas sorption techniques, with each method characterizing a specific pore size range. Ultra small angle neutron scattering and small angle neutron scattering techniques are also useful for the determination of pore connectivity in shales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7] The pore volume of shales can be determined by various techniques such as mercury injection capillary pressure (MICP) porosimetry and grain density/ helium pycnometry, scanning electron microscopy (SEM) images and gas sorption techniques, with each method characterizing a specific pore size range. Ultra small angle neutron scattering and small angle neutron scattering techniques are also useful for the determination of pore connectivity in shales.…”
Section: Introductionmentioning
confidence: 99%
“…Kerogen samples were isolated using chemical methods. 6 Furthermore, high-pressure methane sorption isotherms were determined on both shales and isolated organic kerogen matter to investigate the interrelations between high-pressure sorption capacity, maturity, pore structure and the sorbed gas distribution between organic and inorganic phases.…”
Section: Introductionmentioning
confidence: 99%
“…(1); have complex pore shapes, e.g., Loucks et al (2012); and currently their pore level description is incomplete. Even "pore size" determinations are ill-defined, inconsistent, and often incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, adsorption and MICP analysis should yield similar results. To add to the confusion, Loucks et al (2012), for example, measured pore lengths using FIB/SEM, and reported them as pore sizes.…”
Section: Introductionmentioning
confidence: 99%
“…According to the pore occurrence and pore association with mineral particles under SEM, three types of pore are identified in TYS: interparticle pores, intraparticle pores and organic-matter pores (Fig. 7) (Loucks et al, 2012;Wu et al, 2014;Zhang et al 2016). The SEM evaluation shows that pores in TYS are mainly interparticle pores and organic-matter pores (varying from several nanometers to a few microns), which suggests that mineralogical composition and TOC are the important controlling factors for porosity of the TYS.…”
Section: Porosity and Permeabilitymentioning
confidence: 99%